\[\boxed{\text{1192\ (1192).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ (x - 2)\left( x^{2} + 2x + 4 \right) =\]
\[= x^{3} + 24x\]
\[x^{3} - 8 = x^{3} + 24x\]
\[24x = - 8\]
\[x = - \frac{1}{3}\]
\[Ответ:\ x = - \frac{1}{3}.\]
\[27 - 8x^{3} - 2x \cdot \left( 25 - 4x^{2} \right) = 7\]
\[27 - 8x^{3} - 50x + 8x^{3} = 7\]
\[- 50x = - 20\]
\[x = \frac{2}{5}\]
\[Ответ:x = \frac{2}{5}\text{.\ }\]
\[\boxed{\text{1192.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[2x - 3y = - 6\ \ \ \ \ и\ \ \ \ \]
\[\ 4x + y = a;\ \ \ \ y = 0\]
\[2x - 3 \cdot 0 = - 6\]
\[2x = - 6\]
\[x = - 3.\]
\[4x + y = a\text{\ \ }\]
\[4 \cdot ( - 3) + 0 = a \Longrightarrow \ \ a = - 12\]
\[Ответ:a = - 12.\]